Prosecutorial decision-making regarding offenders' social reintegration programs in intimate partner violence cases. A Portuguese study. - Paulo Vieira-Pinto; José Ignacio Muñoz-Barús; Tiago Taveira-Gomes; Maria João Vidal-Alves; Teresa Magalhães (PLoS ONE, 2022)
Intimate partner violence is one of the most challenging and demanding problems that the criminal justice system has to face. Given the severe consequences of intimate partner violence, it is imperative that intervention from the criminal justice system, regarding perpetrators, be effective to prevent further victimization and recurrences. In Portugal, it is up to the state prosecutor to decide which cases will be subject to a social reintegration program as a pretrial diversion program. This study aims to explore the variables that might influence the state prosecutor's decision-making process. We have examined 283 intimate partner violence cases in which provisional suspension of criminal proceedings was applied. The decision as to whether defendants should be referred for social reintegration program attendance (G1) or not (G2) was made by the state prosecutor. Differences between G1 and G2 were identified: the victim's age, couple living in a current relationship, drug-addicted defendant, intimate partner violence child exposure. However, defendants' unemployment and drug abuse were the only two variables identified as a determinant for state prosecutor decisions. We believe that the effectiveness of state prosecution decision-making would benefit from: (a) systematically taking into account all intimate partner violence risk factors; (b) an index or checklist detailing what science reveals useful in intimate partner violence offenders' social reintegration; (c) rehabilitation solutions based on the needs of each offender instead of a "one-size-fits-all" approach.